Cardiological Syndrome X: Diagnosis and Intensive Care - Yu. V. Shirokikh; S. I. Kuznetsov; N. V. Shapovalova (Общая реаниматология)
Objective: to study the efficacy of the atypical neuroleptic sulpiride in the complex intensive therapy for cardialgic syndrome X (CSX).Subjects and methods. Sixty-six patients with CSX were randomly divided into 2 groups comparable by clinical and history data. Group 1 including 33 patients received traditional intensive antianginal therapy. Group 2 patients were additionally given the atypical neuroleptic sulpiride. The duration of therapy was 4 weeks; thereafter the impact of the therapy performed was evaluated by the time course of changes in anginal symptoms, the frequency of attacks a day, the adaptive capacities of the cardiovascular system, and psychoneurological status.Results. In Group 2 patients taking sulpiri-de in complex therapy, there were more reductions in the number of anginal attacks, their severity and duration. Pain syndrome relief was achieved in the earlier periods. Sulpiride exerted a positive effect on the patients’ psychoneurological status, which made itself evident in the abolishment of the anxious and depressive manifestations of the disease.Conclusion. Reduced symptoms and improved adaptive capacities of the cardiovascular system in CSX patients treated with sulfide leads to the conclusion that the drug used in complex and intensive therapy for CSX is a current effective psychocorrect-ing agent that is well tolerated and safe, which promotes the improvement of final treatment Results.